Studi Kepustakaan Manajemen Pendidikan Karakter Berbasis Mindfulness - Rosnelly Barus; Nurhattati Nurhattati; Kamaludin Kamaludin (Departement of Mathematics Education, 2025)
One of the new approaches widely applied in character development is mindfulness. Mindfulness-based character education management is an approach to managing education that emphasizes the development of students' character through mindfulness practices. The mindfulness approach offers solutions to enhance self-awareness, empathy, and emotional regulation in character education. This study uses a systematic literature review to analyze the application of mindfulness in character education management. The results show that mindfulness supports the development of students' character and helps teachers create a holistic learning environment. This approach requires collaboration from various parties for effective integration within schools. The study concludes that mindfulness-based character education management can create a generation that is academically intelligent as well as emotionally and socially balanced.